Couples facing the "honeymoon period" of Parkinson's disease: A qualitative study of dyadic functioning. Issue 2 (27th October 2022) - Manceau, Charlotte; Constant, Emilie; Brugallé, Elodie; Wawrziczny, Emilie; Sokolowski, Céline; Flinois, Bérengère; Baille, Guillaume; Defebvre, Luc; Dujardin, Kathy; Antoine, Pascal
Abstract: Introduction: The public health issue of the Parkinson's disease (PD) has led to a great deal of research that has highlighted the individual challenges faced by the person with the Parkinson's disease (PwPD) and the caregiving spouse. Few studies, however, have sought to understand the functioning of couples facing PD, by differentiating each stage, each of which has its own issues. In particular, the "honeymoon period", characterized by a symptomatic respite allowed by the effectiveness of treatments for motor symptoms, has been poorly documented, especially at the dyadic level. Design and Method: This qualitative study, based on Interpretative Phenomenological Analysis, aimed to understand the experience of couples and their functioning at this stage. Fifteen couples participated in separate semi‐structured interviews for each partner. The analyses highlighted four dyadic dynamics, which call into question the relevance of the term "honeymoon" to describe the experience of couples. Results: While some couples appear to adjust by means of flexible functioning and a positive reinterpretation of this experience, other dyads oscillate between rigid hyperprotection in the face of perceived distress or a vicious circle of control/avoidance and, in some cases, gradually slipping towards the erosion of the relationship. Discussion: These results show that the relational difficulties suffered by partners at this stage should be taken into account as soon as possible after the diagnosis. Strengthening the communication and the togetherness between partners, as well as working on dyadic emotional regulation, are particularly relevant options for these couples.